Communication—Neutron Radiography of the Water/Gas Distribution in the Porous Layers of an Operating Electrolyser. Issue 11 (1st January 2016) - Seweryn, Jakub; Biesdorf, Johannes; Schmidt, Thomas J.; Boillat, Pierre
Abstract : Neutron radiography was applied to image the water-gas distribution in an operating small scale PEM electrolyser, building up on the anisotropic resolution improvements previously developed for fuel cell imaging. The ability of neutrons to image this distribution across porous materials made of titanium was demonstrated for the first time. This paper presents the procedure's description and limitations, focusing on water content in the porous layers as a function of distance from electrode. A surprising pattern of water content in anodic porous material was observed, which sheds light on the topic of mass transport limitations in PEM electrolysers.